A hybrid genetic algorithm approach to calculating chemical equilibrium and detonation parameters in condensed energetic materials - Zayer, Abdelmoumen; Riedel, Uwe; Warnatz, Jürgen (Combustion theory and modelling, 2010)
We discuss the implementation of genetic algorithms for modelling chemical equilibrium and detonation parameters at the Chapman-Jouguet (CJ) state. This strategy has the advantage that no initial estimate of the equilibrium product distribution needs to be made. It is also an efficient method for finding the global minimum, since for highly non-ideal condensed energetic materials, the calculation of the chemical equilibrium using deterministic algorithms can lead to a local minimum being found instead of a global minimum. This can result in an incorrect prediction of the chemical products distribution. The code was tested for several C-H-N-O energetic materials, namely cyclotrimethyline-trinitramine (RDX), nitromethane (NM), 2,4,6-trinitrotoluene (TNT), and pentaerythritol tetranitrate (PETN). The results obtained using these approaches are in good agreement with the experimental data available in the literature. A comparison with results of other modelling approaches is presented.